2006
DOI: 10.1073/pnas.0600623103
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica cysteine proteases cleave the MUC2 mucin in its C-terminal domain and dissolve the protective colonic mucus gel

Abstract: In order for the protozoan parasite Entamoeba histolytica (E.h.) to cause invasive intestinal and extraintestinal infection, which leads to significant morbidity and mortality, it must disrupt the protective mucus layer by a previously unknown mechanism. We hypothesized that cysteine proteases secreted from the amoeba disrupt the mucin polymeric network, thereby overcoming the protective mucus barrier. The MUC2 mucin is the major structural component of the colonic mucus gel. Heavily O-glycosylated and proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 237 publications
(188 citation statements)
references
References 40 publications
1
182
0
1
Order By: Relevance
“…Recent studies have also highlighted the significance of contact-independent mechanisms in the pathogenesis of amebiasis. For example, CP5 secreted by E. histolytica has been shown to degrade colonic MUC2 mucin 45,46 and to alter innate host defense, thus setting the stage for amebic invasion of the mucosa. Similarly, the roles of other SP components, such as serpins (serine proteinase inhibitors), that manipulate the host pathophysiological function have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also highlighted the significance of contact-independent mechanisms in the pathogenesis of amebiasis. For example, CP5 secreted by E. histolytica has been shown to degrade colonic MUC2 mucin 45,46 and to alter innate host defense, thus setting the stage for amebic invasion of the mucosa. Similarly, the roles of other SP components, such as serpins (serine proteinase inhibitors), that manipulate the host pathophysiological function have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of MUC2 can be influenced by a broad range of mediators including cytokine signals, microbial‐derived products, adrenocorticotropic hormones, autophagic proteins, reactive oxygen species and components of the inflammasome (NOD‐, LRR‐ and pyrin domain‐containing 6) 10, 11, 42, 43, 44, 45, 46…”
Section: Muc2 Biosynthesismentioning
confidence: 99%
“…We have shown that the parasite Entamoeba histolytica can secrete a protease that is able to disrupt the polymeric network of MUC2 mucin (44). This parasite secretes a cysteine protease that is able to cleave human MUC2 mucin at a specific site between two threonines (the sequence RT/T), an odd specificity for a protease.…”
Section: Commensal Bacteria Live In the Outer Mucus Layermentioning
confidence: 99%